1993
DOI: 10.1093/infdis/167.4.932
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Chloroquine: Implications of Drug Resistance for Evaluating Malaria Therapy Efficacy and Treatment Policy in Africa

Abstract: Emphasis on retaining chloroquine as the first-line therapy for Plasmodium falciparum infections in most of sub-Saharan Africa for as long as it remains effective has resulted in widespread reliance on chloroquine in areas where it can have little effect on P. falciparum parasitemia. To address this issue, clinical, parasitologic, and hematologic responses to chloroquine or pyrimethamine/sulfadoxine treatment were assessed among very young children in Malawi (n = 153) and Kenya (n = 73). The median time to res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
178
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(183 citation statements)
references
References 8 publications
5
178
0
Order By: Relevance
“…(Bloland et al 1993). All children р 5 years of age seeking outpatient care at the study facilities with an axillary temperature у 37.5 ЊC underwent screening.…”
Section: Study Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…(Bloland et al 1993). All children р 5 years of age seeking outpatient care at the study facilities with an axillary temperature у 37.5 ЊC underwent screening.…”
Section: Study Protocolmentioning
confidence: 99%
“…In 1973, the World Health Organization (WHO) recommended a 7-day test which incorporated *Use of trade names is for identification only and does not imply endorsement by the U.S. Public Health Service or by the Department of Health and Human Services. clinical response into it's outcome measures (WHO 1973). Although simpler and less expensive to conduct, the major drawback of this procedure was that it did not assess clinical failures after Day 7, which some studies suggested also significantly contributed to malaria-related morbidity and mortality (Khoromana et al 1986;Greenberg et al 1989;Campbell 1991;Bloland et al 1993). A 14-day follow-up study was proposed that permitted, with limited additional cost, a more complete assessment of clinical response.…”
Section: Introductionmentioning
confidence: 99%
“…CQ resistance seems to have spread more rapidly in Eastern than in Western Africa (Bloland et al 1993;Bakyaita 2000). In Burkina Faso the national malaria control programme still recommends CQ as the first and sulfadoxine-pyrimethamine (SP) as the second-line drug.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the criteria on which this decision can be taken are not clear (Bloland et al 1993). The standard methods to assess the efficacy of a given drug can be divided in two broad groups: in vivo and in vitro tests.…”
Section: Surveillancementioning
confidence: 99%